A presença do pai no processo de amadurecimento: um estudo sobre D. W. Winnicott - Fulgencio, Claudia Dias Rosa (2007)
The purpose aim of this paper is to explain Winnicott s concept of what is expected of a father, in terms of his presence and the many roles played by him in the bringing up of a child, during the process of personal maturation, from birth to the stage of Oedipus Complex, keeping in mind healthy up-bringing. Without intending to write a comparative paper that takes into account many psychoanalytic ways of approaching a same topic, I aim to identify aspects of Winnicott s theories, which referring to this theme, can characterize the most important differences between this author and the traditional psychoanalysis concepts. While the traditional psychoanalysis, due to the centerpiece of Oedipus and to the magnitude of the sexuality theory, the father s role was limited mostly overall to the role of an interventionist and a representative of the law, as for Winnicott, the presence of the father in involved implicated since the beginning of life, when questions concerning Oedipus Complex have no meaning whatsoever, and continues changing as the child matures. This paper confirms the thesis that the thoughts reasonings viewpoints thinkings of this author represents a new theoretical and practical foundation from which the human questions, in this case, the presence and role of the father, in the process of maturation, can be understood